Tick resistance. Abrogation of the immune response to Boophilus microplus by systemic injections of cortisone - Babjee, Shaik Mohamed Amin; Willadsen, P.; Johnston, L. A. Y (Malaysian Society of Applied Biology, 1986)
After several experimental exposures to the cattle tick Boophilus mtcroptus, cattle acquired an Immunologically mediated resistance to the tick. Resistant animals expressed a strong immediate hypersensitive reaction to purified tick antigens and developed edematous, eosinophil rich lesions at tick feeding sites. This study showed that such reactions are involved in the rejection of ticks. It was shown that dexamethasone, a potent glucocorticoid, when administered in a therapeutic dose to cattle, induced immunosuppression, as shown by an increase in the number of ticks, reduction in immediate hypersensitivity reactions, and obvious reduction or complete ablation of the cenular infiltration at the feeding sites of the tick larvae